Crowdfunding cultural projects and networking the value creation: Experience economy between global platforms and local communities - Foá, C. (Arts and the Market, 2019)
The purpose of this paper is to investigate how online crowdfunding is strategically applied to artistic productions featuring strong social and cultural values, exploring potential and risks of networking value creation and community engagement. Mission-driven initiatives and their crowdfunding campaigns are analyzed through platform society framework (van Dijk, 2019), considering the business models and marketing strategies that support the scope and intentions of a variety of agents involved within the online networks. Design/methodology/approach A qualitative multiple case-study approach is adopted to sample and analyze in depth significant examples from the most representative crowdsponsoring platforms in Portugal. Agents’ perspectives and practices are collected through semi-structured interviews with campaign creators and platform managers, and complemented by the design of specific business model canvas (Osterwalder and Pigneur, 2010) adapted to crowdfunding projects. Communication strategies and social media marketing are considered, metering agent’s profile and comparing performance and online engagement through profile and official pages observation. Findings Main findings point out that a crowdfunding campaign requires to set up a specific business model and marketing strategy articulation that go beyond the traditional cultural enterprises differentiation criteria, hybridizing them through experience-led marketing logic, extended product conceptualization and a critical cultural entrepreneurship approach. Community engagement operations need to be structured and integrated through online and offline social networks activities, and the value creation is build through shared meaning construction and interpretation between creators and backers, with the support of others agents involved within crowdfunding value network. It also states that the conceptualization of crowdfunding phenomenon as a service ecosystem (Quero and Ventura, 2019) could be extended, to comprehend other actors and power position within intermediation processes, namely, social network and social media platforms corporations, online payments services, online users, legacy media entities and others stakeholders as matchfunding organizations and partners for products’ development and distribution. Research limitations/implications The research design could be improved by adding more quantitative and social analytics data or an international cases comparison to complete these preliminary results. Practical implications The findings could assist arts and media managers as well as cultural agents to adapt their strategies to emergent business and marketing models, strongly influenced by dominant barging positions in the value chain held by new digital intermediaries, and to better explore product levels to strengthen interactions and engagement with communities of interest and supporters for the creation of value. Social implications This paper contributes to elaborate a more accurate scientific knowledge and critical perspective about crowfunding system evolution, concerning both individual and collective agencies, and their implication for different types of agents and networked individuals between institutions (Dutton, 2009). Originality/value This study is unique, as it adopts a multidisciplinary approach and a comprehensive analysis of Portuguese crowdsponsoring phenomenon, and it offers a valid contribution to the analysis of crowdfunding as value-creation network.